314 THE EFFECT OF THE 80-HOUR WORK WEEK ON CONTINUITY OF CARE. (1st January 2005) - McBurney, P. G.; Ector, W. L.; Darden, P. M.
Abstract : Background: In July 2003, the Accreditation Council for Graduate Medical Education mandated limitations on resident work hours. The intent was to improve medical training; the impact is not known. Objective: To determine if the 80-hour work week adversely affects continuity of care for pediatric residents in continuity clinic. Methods: We reviewed computerized medical records for all Medical University of South Carolina pediatric residents for the first 6 academic months of 2002 (before work week regulation) and for the first 6 months of 2003 (after regulation). We calculated continuity of care from the resident's perspective for each individual resident per year using the Continuity for Physician (PHY) formula. We performed t-tests to compare mean continuity for 2002 versus 2003. Multivariate linear regression was used to model the relationship of the work week limitation and continuity from the resident's perspective (PHY). Results: Continuity was calculated for 44 residents in 2002 and 45 in 2003. Overall mean continuity was 52% for 2002 and 50% for 2003 (p = NS); continuity for well child care visits (WCC) was 76% (2002) and 70% (2003) (p < .05). The largest decrease in continuity moving from 2002 to 2003 was seen in the intern year (52% in 2002, 47% in 2003 for all visits; 76%, 68% for WCC visits). In the multivariate model with all visits (WCC and sick), year did not predict continuity. When only WCC visits were considered, year showed a trend towards significance (p = .063) with 2003 having less continuity. In both models, level of training was a significant predictor of continuity. Overall, interns had less continuity than 3rd year residents: 5% points less for all visits and 8% points less for WCC visits only. Conclusion: The 80-hour work week has resulted in decreased continuity in that very important category of well care, and, unfortunately, interns were most affected. Emphasis on continuity in the intern year may need to be increased.